A new species and comparative morphology of Philippine sea biscuits (Echinoidea: Clypeaster) - Mooi, Rich; Noordenburg, Henk Van (Zootaxa, 2021)
A new species of clypeasterid sea biscuit, Clypeaster brigitteae n. sp., is described from material collected in the Philippines at depths between 100 and 200 m. The new taxon increases the number of Clypeaster species recorded from the Philippines to nine, representing nearly a quarter of the world’s diversity of the genus. Other Philippine species include: C. annandalei Koehler, 1922; C. fervens Koehler, 1922; C. humilis (Leske, 1778); C. japonicus Döderlein, 1885; C. latissimus (Lamarck, 1816); C. pateriformis Mortensen, 1948; C. reticulatus (Linnaeus, 1758); and C. virescens Döderlein, 1885. Using type material where available, each of these species is compared and contrasted with C. brigitteae n. sp. in tables consisting of new data derived from general test shape and size, petal structure, food grooves, plate architecture, internal structure, and morphology of spines, pedicellariae, and tube feet.